Kajian Normatif Pertanggungjawaban Pidana Pengurus Bank Terkait Tindak Pidana Perbankan dalam Proses Pemberian Kredit - Agustuti, Dwita; Irawan, Andrie (Indonesian Journal of Law and Justice, 2024)
This study focuses on a normative study of the criminal liability of bank administrators related to banking crimes in the credit granting process. In the banking world, credit management is one of the most crucial aspects, and non-compliance with applicable regulations can result in banking crimes. This study aims to analyze how criminal liability is applied to bank administrators involved in violations of laws related to credit provision. Through a normative juridical approach, this study examines various relevant regulations and cases to evaluate the extent to which criminal law is able to ensnare bank administrators who commit irregularities. The results of the study show that even though regulations have existed, their implementation is often less effective, so improvements in law enforcement and stricter supervision are needed to prevent banking crimes.